Предмет: Алгебра,
автор: Марьяна52
решите пожалуйста, нужно завтра!!
Приложения:
![](https://files.topotvet.com/i/d7b/d7bf2f18291e00090d9c8e4c7faf3118.jpg)
Ответы
Автор ответа:
0
1) x²y/x^8y^7 = 1/x^6y^6
2) - (3x^4y^4)/6x^7 = - y^4/2x³
3) (- 15x²y^7)/(- 9x^9y^8c) = 5/3x^7yc
4) (4x + 16)/x² - 16 = 4(x + 4)/(x - 4)(x + 4) = 4/x - 4
5) (x² - 14x + 49)/(x² - 49) = (x - 7)(x - 7)/ (x - 7)(x + 7) = (x - 7)/(x + 7)
6) (x^8 - x^6)/(x + 1) = x^6(x² - 1)/(x + 1) = x^6(x - 1)(x + 1)/(x + 1) =
= x^6(x - 1)
7) (2 - 2b²)/ (4b² - 8b + 4) = 2(1 - b²)/4(b - 1)(b - 1) = - (1 + b)/ 2(b - 1) =
(1 + b)/(1 - b)
8) (a² + 2ab + b²)/(a² -b²) = (a + b)(a + b)/(a + b)(a - b) = (a + b)/(a - b)
9) (12y³ - 8y²)/(2 - 3y) = 4y²(3y- 2)/(2 - 3y) = - 4y²
2) - (3x^4y^4)/6x^7 = - y^4/2x³
3) (- 15x²y^7)/(- 9x^9y^8c) = 5/3x^7yc
4) (4x + 16)/x² - 16 = 4(x + 4)/(x - 4)(x + 4) = 4/x - 4
5) (x² - 14x + 49)/(x² - 49) = (x - 7)(x - 7)/ (x - 7)(x + 7) = (x - 7)/(x + 7)
6) (x^8 - x^6)/(x + 1) = x^6(x² - 1)/(x + 1) = x^6(x - 1)(x + 1)/(x + 1) =
= x^6(x - 1)
7) (2 - 2b²)/ (4b² - 8b + 4) = 2(1 - b²)/4(b - 1)(b - 1) = - (1 + b)/ 2(b - 1) =
(1 + b)/(1 - b)
8) (a² + 2ab + b²)/(a² -b²) = (a + b)(a + b)/(a + b)(a - b) = (a + b)/(a - b)
9) (12y³ - 8y²)/(2 - 3y) = 4y²(3y- 2)/(2 - 3y) = - 4y²
Автор ответа:
0
1
![1/x^6y^5 1/x^6y^5](https://tex.z-dn.net/?f=1%2Fx%5E6y%5E5)
2
![-y^4/(2x^3) -y^4/(2x^3)](https://tex.z-dn.net/?f=-y%5E4%2F%282x%5E3%29)
3
![-5/(3x^7yc) -5/(3x^7yc)](https://tex.z-dn.net/?f=-5%2F%283x%5E7yc%29)
4
![4(x+4)/[(x-4)(x+4)]=4/(x-4) 4(x+4)/[(x-4)(x+4)]=4/(x-4)](https://tex.z-dn.net/?f=4%28x%2B4%29%2F%5B%28x-4%29%28x%2B4%29%5D%3D4%2F%28x-4%29)
5
![(x-7)^2/[(x-7)(x+7)]=(x-7)/(x+7) (x-7)^2/[(x-7)(x+7)]=(x-7)/(x+7)](https://tex.z-dn.net/?f=%28x-7%29%5E2%2F%5B%28x-7%29%28x%2B7%29%5D%3D%28x-7%29%2F%28x%2B7%29)
6
![x^6(x^2-1)/(x+1)=x^6(x-1)(x+1)/(x+1)=x^6(x-1) x^6(x^2-1)/(x+1)=x^6(x-1)(x+1)/(x+1)=x^6(x-1)](https://tex.z-dn.net/?f=x%5E6%28x%5E2-1%29%2F%28x%2B1%29%3Dx%5E6%28x-1%29%28x%2B1%29%2F%28x%2B1%29%3Dx%5E6%28x-1%29)
7
![2(1-b^2)/[4(1-2b+b^2)]=(1-b)(1+b)/[2(1-b)^2]=(1+b)/[2(1-b 2(1-b^2)/[4(1-2b+b^2)]=(1-b)(1+b)/[2(1-b)^2]=(1+b)/[2(1-b](https://tex.z-dn.net/?f=2%281-b%5E2%29%2F%5B4%281-2b%2Bb%5E2%29%5D%3D%281-b%29%281%2Bb%29%2F%5B2%281-b%29%5E2%5D%3D%281%2Bb%29%2F%5B2%281-b)
![)] )]](https://tex.z-dn.net/?f=%29%5D)
8
![(a+b)^2/[(a-b)(a+b)]=(a+b)/(a-b) (a+b)^2/[(a-b)(a+b)]=(a+b)/(a-b)](https://tex.z-dn.net/?f=%28a%2Bb%29%5E2%2F%5B%28a-b%29%28a%2Bb%29%5D%3D%28a%2Bb%29%2F%28a-b%29)
9
![4y^2(3y-2)/[-(3y-2)]=-4y^2 4y^2(3y-2)/[-(3y-2)]=-4y^2](https://tex.z-dn.net/?f=4y%5E2%283y-2%29%2F%5B-%283y-2%29%5D%3D-4y%5E2)
2
3
4
5
6
7
8
9
Похожие вопросы
Предмет: Алгебра,
автор: alenasadrieva84
Предмет: Математика,
автор: emilqasimov205
Предмет: Информатика,
автор: lion3764
Предмет: Обществознание,
автор: kiskairisksa
Предмет: Химия,
автор: Виктори2506